An assessment of community pharmacists’ responses to hypothetical medical emergency situations - McMillan, S.; Hattingh, Laetitia; King, M. (John Wiley & Sons Ltd., 2012)
Objective: To investigate community pharmacists’ proposed actions in hypothetical medical emergency situations in South-East Queensland, Australia. Method: A survey was posted to 151 Gold Coast and Toowoomba community pharmacies in October 2009. Pharmacists were asked to document their opinions regarding the pharmacist’s role in medical emergencies and to respond to statements associated with two hypothetical medical emergency situations: an anaphylaxis and an asthma attack. Key findings: Forty-five pharmacists responded to the survey (29.8%). In response to a hypothetical situation involving an asthma attack, 41 pharmacists (91.1%) agreed that they would assist the asthmatic person to administer salbutamol through a spacer, with 28 pharmacists (62.2%) confident in treating an asthma attack in the pharmacy. In comparison, only 21 pharmacists (21/38; 55.3%) agreed to administer an adrenaline auto-injector (Epi-Pen) for a child experiencing an anaphylaxis, with nine respondents (9/38; 23.7%) indicating that they would ask the mother for directions in a situation where they were unsure how to administer it. There were comments questioning whether indemnity insurance covers pharmacists for medicine administration, and 12 pharmacists (12/38; 31.6%) indicated that if they were unsure about insurance cover they would ask the mother to administer the adrenaline. Conclusion: Pharmacists’ responses to administering medications in hypothetical medical emergencies were variable. The cause of this variation is multi-factorial and likely to include familiarity with the medication, its safety profile and uncertainty about the pharmacist’s role and responsibilities in these situations. Further clarification, training and guidelines are needed in order to address this.